The Effectiveness of Using English Songs to Teach Vocabulary to Fifth Grade Students - Benedikta Ria Saraswati Cahyaningrum (STKIP Taman Siswa Bima, 2025)
The researcher made this research to investigate the effectiveness of using English song in teaching vocabulary to fifth-grade students at SDK Santa Maria Tulungagung during the academic year 2024/2025. The study employed a quasi-experimental design with two groups: an experimental group taught using English songs and a control group taught using conventional methods. Data were collected through pre-tests and post-tests, and analyzed using the Independent Sample T-test. The results showed that although the experimental group achieved a slightly higher mean post-test score compared to the control group, the statistical analysis indicated no significant difference between the two groups (p > 0.05). Thus, English songs did not significantly improve students' vocabulary mastery compared to conventional teaching methods. However, descriptively, the use of English songs created a more engaging and motivating classroom atmosphere. Therefore, while English songs may not drastically enhance vocabulary mastery in a short period, they remain a valuable tool for maintaining students' interest and enthusiasm in learning.